PHARMACOLOGICAL CHANGES IN THE CELLULAR STRUCTURE OF THE HUMAN BODY (American Journal of Interdisciplinary Research and Development, 2022)
In this paper, quantitative changes in lipid content in the liver mitochondria were measured at different times after heliotrin was administered to rats to determine the pathogenetic significance of hepatitis in the liver.